2018
DOI: 10.1007/s10815-018-1152-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 12-month dehydroepiandrosterone supplementation on the menstrual pattern, ovarian reserve markers, and safety profile in women with premature ovarian insufficiency

Abstract: Our results do not support any significant improvement in ovarian function by 12-month DHEA supplementation in women with POI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Six eligible studies were selected in this review, including one randomized controlled trial and five prospective observational cohort studies. Four strategies for ovarian function recovery were used, including PRP treatment ( 16 , 27 ), DHEA supplement ( 28 , 29 ), HRT treatment ( 30 ), and intraovarian transplantation of autologous adipose-derived mesenchymal stromal cells treatments ( 31 ). The sample size of the individual studies ranged from 9 to 311, with a total of 421 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six eligible studies were selected in this review, including one randomized controlled trial and five prospective observational cohort studies. Four strategies for ovarian function recovery were used, including PRP treatment ( 16 , 27 ), DHEA supplement ( 28 , 29 ), HRT treatment ( 30 ), and intraovarian transplantation of autologous adipose-derived mesenchymal stromal cells treatments ( 31 ). The sample size of the individual studies ranged from 9 to 311, with a total of 421 patients.…”
Section: Resultsmentioning
confidence: 99%
“…A prospective observational study of 31 Chinese women with POI conducted by Wong et al ( 28 ) had evaluated the long-term effect of DHEA in patients with POI. All patients had a normal karyotype and 19 (61.3%) patients had used HRT previously and HRT was withheld for at least two months before DHEA treatment, 24 (77.4%) patients were amenorrhoeic, and 7 (22.6%) patients were oligomenorrhoeic.…”
Section: Resultsmentioning
confidence: 99%
“…With this in mind, 38 women with POI were recruited to an observational trial of 12 months of DHEA supplementation (25 mg three times a day), the aim being to allow sufficient time for any effect on follicle recruitment to become apparent. Thirty-one women completed the study and there was no effect on markers of ovarian reserve or menstrual pattern 138 .…”
Section: Dehydroepiandrosteronementioning
confidence: 99%
“…The cause of the primordial follicular loss is not yet known, but this definite result has been tried to slow down with some adjuvant treatments such as dyhydroepiandrostenodione (DHEA) or testosterone. These molecules are synthesized by the ovary and the adrenal gland and enhance the effect of gonadotropin on follicle development through insulin-like growth factor 1 (IGF-1) (16,17). Some authors have concluded that the use of DHEA before IVF can increase ovarian reserve markers and ovarian response to ovarian stimulation (18)(19)(20)(21).…”
Section: Dhea and Testosteronementioning
confidence: 99%
“…Some authors have concluded that the use of DHEA before IVF can increase ovarian reserve markers and ovarian response to ovarian stimulation (18)(19)(20)(21). However, in many studies, the use of DHEA supplements in ovarian reserve or pregnancy rates before IVF treatment has not been observed (16,17). Qin et al (17), in a meta-analysis of pretreatment with DHEA, have shown that the pregnancy rates could increase (OR: 1.47, 95% CI: 1.09-1.99), but decrease (OR: 1.08, 95% CI: 0.67-1.73) if only randomized controlled trials (RCTs) were included, which reveals that pretreatment with DHEA has no effect on pregnancy rates, number of eggs, fertilization, and miscarriage rates.…”
Section: Dhea and Testosteronementioning
confidence: 99%